The phenomenon of mobbing among young employees in relation to the size of the organization in Poland - Jarosz, Szymon; Gozdecki, Karol (The journal of contemporary issues in business and government, 2021)
The article is deals with the phenomenon of mobbing affects young people taking their first steps on the labour market in relation to the size of the organization. It is obvious that mobbing has a deep impact on individuals. Nevertheless, it also has profound, consequences for management in the organization, quality of management and atmosphere in the organization, which consequently translates into the performance of the whole organization. The objectives of the article were achieved by using the survey questionnaire research tool. The conclusions of the article can provide important guidance to management practitioners, giving an insight into the situation of mobbing depending on the size of the organization.